Thinking through RE: 21st century faiths, beliefs and individuals ; [an active approach to Key Stage 3 RE using thinking skills] - Osborne, Eileen; Mitchell, Joanne (Folens, 2007)
Summary: Ready-made lessons with a strong emphasis on delivering thinking skills and strategies for active learning. Topics are presented in short sections, which can represent one or more lessons' worth of material. All the material in the file is supplied in a customisable format on the CD-ROM, together with the images, quotes and sources from the file to allow real flexibility of use on a whiteboard.